Taksonomiczna analiza poziomu zrównoważonego rozwoju województw w Polsce - Wiszniewska, Elżbieta (Taxonomic Analysis of the Sustainable Development Level of Voivodships in Poland, 2008)
The main goal of this article is to estimate the level of the sustain development of voivodships in Poland. Additionally, there were found answers for such questions: is the range and the rate of sustain development equal in every region, and which provinces are on higher and which on lower level of "eco-development”? The analysis was based on defined environmental indicators. Voivodships were aggregated with regard to the level of sustain development in years 2000 - 2006. The proposed diagnostic variables were unitarised. Afterwards there were constructed synthetic indicators of development called meta-variables. The level of voivodships "ecological attraction" was measured with the pattern of development method (measurements of development were also created). Amongst voivodoships there were assigned the theoretical pattern and anti-pattern of sustain development. GUS was the source of all statistics.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 371-380